Formulation and Evaluation of Flurbiprofen Solid Dispersions Incorporated Buccal Patches (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Flurbiprofen is an anti-inflammatory drug used in treating rheumatoid arthritis and ankylosing spondylitis. The present work is aimed at overcoming the deprived solubility of flurbiprofen by solid dispersion (SD) technique. The current paper is the continuance of the published solid dispersion by considering the best final optimized formulation containing flurbiprofen drug: AQOAT AS: SLS as drug: polymer: surfactant in 1:5:2 ratios, and incorporating it into buccal patches to overcome the gastric side effect and attaining sustained drug release. In this study 15 buccal patches were formulated by adopting solvent casting technique using polymers like polyvinyl hydroxyethylcellulose (HEC), hydroxypropryl methyl cellulose E15 (HPMC E15), polyvinyl pyrrolidone (PVP), carbopol and analyzed for the drug content, drug diffusion, in-vivo dissolution and stability studies. All SD loaded patches displayed superior drug release (95% to 99.96%) over 12 h. The formulation BP14 showed excellent drug release extended over 12 h with drug release of 99.96% whereas marketed formulation which is sustained release Tablet showed 96.86% drug release within 6 h. The drug release kinetics show that the buccal patches follow zero order release kinetics with correlation coefficient (R2) ranging between 0.905-0.971 and BP14 formulation shown best R2 value. All the formulations exhibited best fit to Higuchi model with R2 ranging between 0.9911 – 0.9962 indicating drug release by diffusion process. The results conclude that buccal patches are superior alternatives for flurbiprofen that facilitates enhanced drug release for prolonged period of time in the effective management of rheumatoid arthritis.